Desmoid tumors: who, when and how to treat?. Issue 4 (July 2022) - Mikhael, Rabih; Smith, Myles; Tzanis, Dimitri; Watson, Sarah; Miah, Aisha B.; Bonvalot, Sylvie
Abstract : Purpose of review: The objective of this article is to summarize new treatment strategies of desmoid tumors. Recent findings: Desmoid tumor has an unpredictable evolution that may spontaneously regress or stabilize. A shift toward an initial frontline active surveillance has been acknowledged by experts. Surveillance monitoring should be performed frequently after the diagnosis to avoid missing a significant progression and then spaced in case of stabilization. Treatment is based on significant tumor growth or symptoms. Recent guidelines recommend commencing medical treatment. Kinase inhibitors and cytotoxic agents are the two classes of drugs where studies included progressive desmoid tumors and should be selected to guide medical practice. In a randomized trial, 2 years progression-free survival (PFS) was significantly better in the sorafenib group (81 versus 36% in the placebo group). In another randomized phase 2, 6 months PFS was 83.7% with pazopanib versus 45% with methotrexate and vinblastine. In a retrospective study, including progressive desmoid tumors, methotrexate + vinca alkaloids achieved 75 months median PFS. Cryotherapy is an alternative option in desmoid tumors with compatible locations and tumor sizes. Following medical treatment or cryotherapy failure, superficial sites represent the best indications for surgery in cases of continuous progression. In the event of a contra-indication or failure of medical treatment, in locations where surgery would be mutilating and incomplete, radiotherapy is an effective option. Summary: Active surveillance with planned imaging has become the first-line management in desmoid tumor.